Solidaritas Sosial dan Resiliensi Masyarakat Kajen Bantul Pasca Covid-19 - Lulu Sylvianie; Fattah Setiawan Santoso (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The Covid-19 pandemic has affected the resilience of informal sector workers in the Kajen Bantul community. As they share many similarities, according to Emile Durkheim’s theory, they may own social solidarity. This research questioned the relationship between social solidarity and the ability to create social and economic resilience using qualitative method. The data were collected through participatory observations and interviews with the members of Kajen society especially those working in pottery making. Using Durkheim’s theory, this research finds that the latter works more obviously between two solidarities in Kajen: organic and mechanic solidarity. There is no relation between mechanic solidarity and economic resilience as the collective consciousness to build societal organization for the safety net during post Covid-19 was still absent. In managing their resilience, the people are still in the stage of immediate coping mechanism yet unable to design a more comprehensive system of resilience. Therefore, it is suggested that a societal organization is created for that matter.